2007
DOI: 10.1017/s1368980007000973
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and overweight trends in Catalonia, Spain (1992–2003): gender and socio-economic determinants

Abstract: Objective: To evaluate the trends of overweight and obesity prevalences in the population of Catalonia, Spain, aged 18-75 years, and the influence of socio-economic determinants on these prevalence trends. Design: Analysis based on data from two representative population-based cross-sectional surveys. Setting: Data from the two Evaluations of Nutritional Status in Catalonia (ENCAT 1992-93 and ENCAT 2002-03), Spain. Weights and heights were obtained by direct measurement in standardised conditions by trained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 35 publications
7
32
3
4
Order By: Relevance
“…[15] which is similar to our finding to some extent. our study differ from a study done Spain where all the values of obesity and abdominal obesity is less (16.6% in males and 15.2% in females ) [16] also Iran study had less prevalence of obesity (34.8%)and less abdominal obesity (28.3) but it is similar to our study in that female had higher prevalence of abdominal obesity than males [17] Netherlands study showed very low prevalence of obesity in compared to our study, it was 4 and 6% in men and women, respectively [18] …”
Section: Discussioncontrasting
confidence: 99%
“…[15] which is similar to our finding to some extent. our study differ from a study done Spain where all the values of obesity and abdominal obesity is less (16.6% in males and 15.2% in females ) [16] also Iran study had less prevalence of obesity (34.8%)and less abdominal obesity (28.3) but it is similar to our study in that female had higher prevalence of abdominal obesity than males [17] Netherlands study showed very low prevalence of obesity in compared to our study, it was 4 and 6% in men and women, respectively [18] …”
Section: Discussioncontrasting
confidence: 99%
“…If the Western people could switch to the Mediterranean diet, some cancers would be decreased (Trichopoulou et al, 2000). The increased colorectal cancer incidence rates in some countries in Asia, Eastern Europe and Spain are associated with changes in dietary and lifestyle factors (Garcia-Alvarez et al, 2007;de Kok et al, 2008;Martin et al, 2008;Center et al, 2009a;2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Though at relatively low levels nationwide, the mortality rates of colorectal cancer and female breast cancer have been increasing over the past 30 years in Guangxi, and these two cancers have been a growing threat to local residents and women, given their long-term upward trend. Such unfavorable trends in colorectal cancer are thought to reflect a combination of factors including changes in dietary patterns, obesity, physical inactivity, excessive alcohol consumption and an increased prevalence of smoking (García-Álvarez et al, 2007;Ferrari et al, 2007;Center et al, 2009). The increasing mortality rate of female breast cancer largely stems from reproductive and hormonal factors, unhealthy lifestyle and obesity also increase the risk of breast cancer (Colditz et al, 2005;Hulka et al, 2008).…”
Section: Discussionmentioning
confidence: 99%